2021
DOI: 10.1002/jev2.12063
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic profile of melanoma cell‐derived small extracellular vesicles in patients’ plasma: a potential correlate of melanoma progression

Abstract: Molecular profiling of small extracellular vesicles (sEV) isolated from plasma of cancer patients emerges as promising strategy for biomarkers discovery. We investigated the proteomic profiles of sEV immunoselected using anti‐CSPG4 antibodies from 15 melanoma patients’ plasma. The proteomes of sEV separated into melanoma cell‐derived (MTEX) and non‐malignant cell‐derived (NMTEX) were compared using high‐resolution mass spectrometry. Paired analysis identified the MTEX‐associated profile of 16 proteins that dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
55
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(57 citation statements)
references
References 51 publications
2
55
0
Order By: Relevance
“…Besides, this molecule profile was also detected in biopsies of melanoma patients with a poor prognosis, thus representing a specific signature stage-disease related [ 66 ]. In line with this study, some of these proteins (GNS, CFL, HSP90AB1) were found upregulated in Exo derived from plasma of melanoma patients when compared to healthy donors [ 69 ]. These results suggest that acidic Mexo are carriers of specific molecules associated with the advanced stage of the disease, and therefore they can be considered a potential reservoirs of prognostic biomarkers.…”
Section: How Acidity and Hypoxia Modulate Melanoma Progression Through Mexosupporting
confidence: 70%
“…Besides, this molecule profile was also detected in biopsies of melanoma patients with a poor prognosis, thus representing a specific signature stage-disease related [ 66 ]. In line with this study, some of these proteins (GNS, CFL, HSP90AB1) were found upregulated in Exo derived from plasma of melanoma patients when compared to healthy donors [ 69 ]. These results suggest that acidic Mexo are carriers of specific molecules associated with the advanced stage of the disease, and therefore they can be considered a potential reservoirs of prognostic biomarkers.…”
Section: How Acidity and Hypoxia Modulate Melanoma Progression Through Mexosupporting
confidence: 70%
“…In recent years, exosomes have emerged as an important liquid biopsy tool for a variety of malignant tumors ( 24 ). With the development of mass spectrometry and other detection technologies, the protein composition of exosomes has been constantly identified; some of these are already used as tumor biomarkers due to their stability and specificity ( 20 , 25 ). Amongst them, Glycosyl-Phosphatidyl-Inositol (GPI) anchored proteins (GPI-APs) are attractive as a source of exosomal candidates ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…(F) ROC curves analysis for the detection of PHCCA using exosomal Cripto-1 in both CA19-9 and CEA negative individuals. technologies, the protein composition of exosomes has been constantly identified; some of these are already used as tumor biomarkers due to their stability and specificity (20,25). Amongst them, Glycosyl-Phosphatidyl-Inositol (GPI) anchored proteins (GPI-APs) are attractive as a source of exosomal candidates (26).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of cancer may indeed influence the plasma EV population, as also recently found by Pietrowska et al, who captured melanoma and non-melanoma-derived EV in the plasma of 15 patients, comprising also stage I-II patients at diagnosis. According to their data, in plasma of these patients they could also capture melanoma antigen CSPG4, indicating the presence of melanoma-derived EV at the systemic level, despite the early stage of disease [61]. Thus, we are confident that our results-although gathered from a small cohort and not validated, a limitation of our study-may nonetheless advance the field, even if still far from translation into the clinical practice.…”
Section: Discussionmentioning
confidence: 69%
“…Notably, in this context, EV have generated enthusiasm due to their potential utility in liquid biopsies [59,60]. Plasma-derived EV from cancer patients could reflect in part the molecular and genetic contents of the releasing parent tumor cells, and thus their protein contents may be informative [61]. Similarly, lipid metabolic alterations of tumor cells have attracted major interest [62].…”
Section: Discussionmentioning
confidence: 99%